PENENTUAN KUALITAS AIR DANAU BATUR MELALUI INDEKS PENCEMARAN BIOLOGIK DAN NON BIOLOGIK - Nyoman Wijana (Bumi Lestari Journal of Environment, 2010)
This research is done in Lake Batur to know the water quality of Lake Batur this time through biological and non biological pollution index. The population of this research is all water in the lake and the sample is the water taken from Trunyan, Toya Bungkah, Kedisan and Songan Villages. Systematic sampling is employed to take the sample. The data are analyzed by ecologically statistic and its result is compared to the standard water quality according to its functions. The result shows (1) the water quality of Lake Batur based on non biological and biological pollution index shows degradation phenomena; (2) IPB, NVC, and Total Coliform results show that there is water pollution; (3) the physical and chemical aspects (e.g. pH and temperature), do not show pollution yet, meanwhile the dissolved oxygen (DO) shows the classification of medium pollution; and (4) the source of pollution can be predicted through farming, fishery, household, tourism activities and natural pollution source.